2009
DOI: 10.1590/s1516-35982009000100021
|View full text |Cite
|
Sign up to set email alerts
|

Consórcio capim-braquiária e milho: comportamento produtivo das culturas e características nutricionais e qualitativas das silagens

Abstract: Nesta pesquisa, o objetivo foi avaliar as diferenças entre silagens de culturas exclusivas ou do consórcio de milho e capim-braquiária, além de dois arranjos de semeadura do consórcio (duas fileiras de capim-braquiária nas entrelinhas do milho; e semeadura de capim-braquiária a lanço nas entrelinhas do milho). Avaliaram-se as produções de matéria seca (MS), proteína bruta (PB) e nutrientes digestíveis totais (NDT) por área e as características qualitativas das silagens (teores de PB, NDT, FDN, lignina e carboi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 26 publications
2
15
1
6
Order By: Relevance
“…Based on these results, it can be suggested that the presence of sorghum in intercropping systems raised the TDN. A similar finding was observed by Leonel et al (2009), who reported that the average TDN content of silages in intercropping systems was higher than those achieved in the silages of grasses in monocrop.…”
Section: Acta Scientiarum Animal Sciencessupporting
confidence: 88%
“…Based on these results, it can be suggested that the presence of sorghum in intercropping systems raised the TDN. A similar finding was observed by Leonel et al (2009), who reported that the average TDN content of silages in intercropping systems was higher than those achieved in the silages of grasses in monocrop.…”
Section: Acta Scientiarum Animal Sciencessupporting
confidence: 88%
“…Low concentrations of lignin is considered relevant to improving the nutritional value of forage and increased consumption of silage by animals, because the lignin is associated with indigestible food, however, more important than its content is its structural arrangement in the cell wall forage (JUNG;DEETZ, 1993). However, there have been approached the lignin content in tropical grasses as depressive fraction of food (LEONEL et al, 2009), therefore, low levels of lignin allow better use of the fiber by microorganisms in the rumen (RIBEIRO et al, 2008). Guimarães Junior (2005a) evaluating the fibrous fractions of silages of three pearl millet genotypes, observed lignin concentration of 4.01, 3.34 and 4.31% for the CMS-1; BRS-1501 and BN-2 genotypes, respectively, after the fermentation period of 56 days.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of 15% of millet meal increased by 11% the TDN content when compared with no application of this additive on silage fermentation. In a study on qualitative and nutritional characteristics of Brachiaria grass silage, Leonel et al (2009) The pH of silages was not affected (P>0.05) by the interaction of cultivars and levels. There was a significant effect of cultivar (Table 2) and levels of millet meal inclusion (Figure 4b).…”
Section: (2007)mentioning
confidence: 92%
“…However, it has been approached the lignin content in tropical grasses as depreciative fraction of food (Leonel et al, 2009). …”
Section: (2007)mentioning
confidence: 99%